Political communication strategies of local politicians in the political constellation of legislative elections at the Regency/City level - Fadillah, Dani; Nurhidayah, Sitti (COMMICAST, 2024)
This research aims to determine how local politicians carry out the political communication strategy to win the political constellation of district/city-level legislative elections. This research uses a qualitative approach; in collecting data, researchers chose politicians from the Gerindra party named Muhasbih, who fought in the Polewali Mandar district legislative elections in the 2024 elections, as research subjects. Researchers conducted in-depth interviews with the politician and his success team, who actively participated in winning the 2024 election. The results of this study indicate that effective communication in winning political constellations in legislative elections at the district/city level requires understanding the audience and local political dynamics. Through in-depth interviews with politicians and their success teams, it was found that the success of political communication strategies lies in delivering relevant, measurable, and understandable messages to voters. In addition, it was found that the presence of politicians in the field and direct interaction with voters is very influential in building personal relationships and trust. This suggests that the human side and direct involvement in local politics play a crucial role in creating emotional bonds between politicians and voters, which can influence voters' decisions inside the voting booth. Furthermore, the results of this study also highlight the need for adopting strategies that are dynamic and responsive to political and technological developments. Although local politicians such as Muhasbih do not use social media in their campaigns, it is important to continuously monitor trends and adapt political communication strategies as needed as the political environment changes.